Properties of aluminum matrix Nano composites prepared by powder metallurgy processing - Amal E. Nassar; Eman E. Nassar (Journal of King Saud University: Engineering Sciences, 2017)
Pure aluminum Nano composite reinforced with Nano titanium dioxide was produced by powder metallurgy route. Measurements of tensile strength, hardness, and density showed that the porosity and the tensile strength of composites increased with an increase in volume fraction of nanoparticles; however ductility of aluminum was decreased. Wear test revealed that composites offer superior wear resistance compared to alloy.